Subsidy Review of Inland Waterways Pioneer at KMP. Lohoraung in Likupang - Biaro Tracking, North Celebes Province - Hartanto Hartanto; Argo Victoria Ong; Meila Permata Sari (Politeknik Transportasi Sungai, Danau dan Penyeberangan Palembang, 2019)
The ferry port of Likupang is the path that connects the island of Celebes with Sitaro Islands District, which is managed by the Department of Transportation North Minahasa. The ferry port of Likupang still a pioneer and still get subsidies from the government each year. In the calculation of subsidies to local authorities still use the subsidy calculation based Director General of Land Transportation Regulation Number SK.218 / AP.204 / DrJD / 2018 on Income and Cost Component Counts In Operation Activity ferries transport Pilot which has been repealed and replaced by Director General of Land Transportation Regulation Number SK.5856 / AP.204 / DrJD / 2018 regarding Calculation and Transport Subsidy Funding Procedures Pioneer Crossing. Therefore, it warrants further evaluation regarding ferry transport subsidies KMP Lohoraung in Likuoang-Biaro Tracking North Celebes using the calculation ofSK 5856 / AP.201 / DrJD / 2018. The research method used is observation and interview vessel operators as well as literature. Based on the analysis of the government should provide subsidy in accordance with applicable regulations, namelyDirector General of Land Transportation Regulation Number SK.5856 / AP.204 / DrJD / 2018 on Procedures Calculation and Pioneer Ferries transport Subsidy Funding for Rp.3.145.418.407, - and writer suggest the making of leaflets in the form of a schedule and departure times are propagated to the service user to increase the size of the load factor so that the vessel can potentially increase the income of the ship itself.